Polyphenol–Poloxamer Self‐Assembled Supramolecular Nanoparticles for Tumor NIRF/PET Imaging. Issue 15 (14th May 2018) - Wang, Xinyu; Yan, Junjie; Pan, Donghui; Yang, Runlin; Wang, Lizhen; Xu, Yuping; Sheng, Jie; Yue, Yuanyuan; Huang, Qianhuan; Wang, Yanting; Wang, Rongrong; Yang, Min
Abstract: Self‐assembled supramolecular nanoparticles have remarkable benefits in bioimaging and drug delivery. Here it is first reported that polyphenol and poloxamer self‐assemble supramolecular nanoparticles (PPNPs). PPNPs are fabricated by multivalent hydrogen bonding between tannic acid and Pluronic F‐127 together with hydrophobic interactions of poly(propylene oxide) chains, to be applied in tumor near‐infrared fluorescence (NIRF) imaging and positron emission tomography (PET) imaging. With near‐infrared fluorescent dyes such as IR780 encapsulated via hydrophobic interactions, PPNPs are used in NIRF imaging. PPNPs with excess phenolic hydroxyl groups chelating positron emitting radionuclide 89 Zr function as a PET contrast agent. The in vivo results show surprisingly higher fluorescence intensity in tumors than in other tissues. In addition, PPNPs exhibit good biocompatibility in various cell lines and do not induce hemolysis in vitro. In this study, it is demonstrated that biodegradable and biocompatible PPNPs are an excellent bimodal contrast agent for in vivo tumor imaging. Abstract : Polyphenol–poloxamer supramolecular nanoparticles are fabricated with a facile self‐assembly process. Near‐infrared fluorescence (NIRF) dye IR780 and positron emitting radionuclide 89 Zr can be loaded by taking advantage of the hydrophobic center and excess phenolic hydroxyl in the nanoparticle. This supramolecular nanoparticle obtains excellent tumor NIRF and positron emission tomography imaging abilities.